Ferrocene containing redox-responsive poly(2-oxazoline)s. Issue 11 (18th January 2021) - Borchers, Philipp S.; Dirauf, Michael; Strumpf, Maria; Görls, Helmar; Weber, Christine; Hager, Martin D.; Schubert, Ulrich S.
Abstract : A novel monomer, 2-ferrocene-ethyl-2-oxazoline, was copolymerized with 2-alkyl-2-oxazolines. The resulting well-defined polymers retained the reversible redox-activity of ferrocene, thus proving the absence of any unfavorable side reactions. Abstract : A new monomer, 2-ferrocene-ethyl-2-oxazoline, was copolymerized with 2-alkyl-2-oxazolines. The cationic ring opening polymerization (CROP) of 2-oxazolines allows the synthesis of well-defined copolymers with adjustable molar masses as well as end-group control, which was also evident from kinetic studies. The utilization of this new comonomer led to redox-active polymers as proven by UV-VIS-measurements and cyclic-voltammetry.